2014
DOI: 10.1002/anie.201308609
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Charge Density Study of a Silylone

Abstract: An experimental and theoretical charge density study confirms the interpretation of (cAAC)2Si as a silylone to be valid. Two separated VSCCs present in the non-bonding region of the central silicon are indicative for two lone pairs. In the experiment, both the two crystallographically independent Si-C bond lengths and ellipticities vary notably. It is only the cyclohexyl derivative that shows significant differences in these values, both in the silylones and the germylones. Only by calculating increasing spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 125 publications
(54 citation statements)
references
References 75 publications
1
52
0
1
Order By: Relevance
“…demonstrated the use of NHCs to stabilize the silicon(0) compound (IPr)Si=Si(IPr) (IPr=:C{N(Ar)CH} 2 with Ar=2,6‐diisopropylphenyl) . Our group has previously reported the synthesis and analysis of cAAC‐stabilized acyclic silylone and germylone . Driess and co‐workers used a bis‐N‐heterocyclic carbene (bNHC) for the stabilization of a cyclic silylone and germylone ,.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated the use of NHCs to stabilize the silicon(0) compound (IPr)Si=Si(IPr) (IPr=:C{N(Ar)CH} 2 with Ar=2,6‐diisopropylphenyl) . Our group has previously reported the synthesis and analysis of cAAC‐stabilized acyclic silylone and germylone . Driess and co‐workers used a bis‐N‐heterocyclic carbene (bNHC) for the stabilization of a cyclic silylone and germylone ,.…”
Section: Methodsmentioning
confidence: 99%
“…The bond dissociation energies (BDEs) of the recently reported related tetrylone complexes, for instance, the more bulky [W(CO) 5 ‐{C(PPh 3 ) 2 }] to [W(CO) 5 ‐{Pb(PPh 3 ) 2 }] tetrylone complexes, exhibited values that increase from lighter to heavier homologues, and the tetrylone with the tungsten tetracarbonyl gave a similar BDE trend but with a smaller alteration for the [W(CO) 4 ‐{C(PPh 3 ) 2 }] to [W(CO) 4 ‐{Pb(PPh 3 ) 2 }] complexes . We note that the tetrylones always have two lone‐pair orbitals available for donation , , . By contrast, the transition metal complexes that carry carbene and analogues NHE s (E = C to Pb) always exhibit decreased bond strength because carbene and its analogues have only one lone pair for donation , .…”
Section: Introductionmentioning
confidence: 92%
“…Several recent theoretical studies suggested that the bonding in CL 2 is not limited to the carbon as the central atom, and can be extended to the heavier homologues EL 2 with E = Si to Pb, , in which the ligands EL 2 are strong σ‐donors and weak π‐donor , . It has also been known that investigations on the heavier analogues of carbones EL 2 , such as silylones, germylones, stannylones, and plumbylones (E = Si, Ge, Sn, Pb), have also been widely conducted recently because of the special properties of the structures of these complexes , , , . Compared to carbones (CL 2 ), carbenes (CR 2 ) have just a single electron lone pair at the carbon central atom and have two electron‐sharing bonds (CR) to the carbon atom in the 3 P ground state …”
Section: Introductionmentioning
confidence: 99%
“…reported NHC‐coordinated silicon dibromide NHC→SiBr 2 and silicon diiodide NHC→SiI 2 from the reduction of [(SiX 3 )NHC]X (X=Br, I) by using two equivalents of KC 8 . Recently, we demonstrated that cAAC (cAAC = C(CH 2 )(CMe 2 ) 2 N‐2,6‐ i Pr 2 C 6 H 3 )) reacts with NHC→SiCl 2 and forms the biradical (cAAC) 2 SiCl 2 , further reducible to a silylone . After the successful isolation of the base‐coordinated SiCl 2 , we focused on the synthesis of a stable silicon difluoride.…”
Section: Methodsmentioning
confidence: 94%